Obsessive-compulsive symptoms in patient with schizophrenia: The influence of disorganized symptoms, duration of schizophrenia, and drug resistance - Panov, Georgi; Panova, Presyana (Frontiers in Psychiatry, 2023)
Background: Schizophrenia is a chronic mental disorder with many-faced clinical presentation. Resistance to treatment is observed in a significant proportion of the patients. Obsessive-compulsive symptoms are often observed in patients with schizophrenia. The assessment of the relationship between the presence of obsessive-compulsive symptoms, peculiarities in the clinical picture and resistance to therapy in patients with schizophrenia is the basis for the correct approach to therapeutic interventions. Methods: A study was conducted on 105 patients with schizophrenia who met the inclusion and exclusion criteria used. Of them, 39 are men and 66 are women. The evaluation of the effectiveness of the treatment performed at the 12th week of therapy showed that 45 were resistant to the applied therapy, while the remaining 60 respond-ed. Clinical assessment of patients was performed using the PANSS and BPRS scales. Assessment of obsessive-compulsive symptoms (OCS) was conducted with the Di-mensional obsessive-compulsive symptoms scale (DOCS). Results: In patients with resistant schizophrenia, the registered obsessive-compulsive symptoms were in the moderate values of the scale, and in patients in clinical remission, the obsessive-compulsive symptoms were mildly expressed. We found a statistically significant relationship between the severity of OCS and the disorganized symptoms and the duration of the schizophrenia process. No differences were found in the expression of OCS in patients of both sexes. Conclusion: We found increased values of obsessive-compulsive symptoms in patients with resistant schizophrenia. These values correlated with the PANSS disorganized subscale and the duration of schizophrenia.